Webinar academic writing: writing is healing - Michael Hadjaat; Rizky Yudaruddin; Ady Wardana; Dea Ayu Mardhotillah; Putri Naufha Soraya; Reisya Amalia Nur Fitriani (Faculty of Economics and Business Mulawarman University, 2022)
Academic writing is an important thing among academics such as students and lecturers. There are so many uses for academic writing, both for the purposes of final assignments such as thesis, research, and the need for applying for scholarships. However, there are many things that need to be considered in academic writing. Grammar is one of the components of writing that is very important to note, there are often many grammatical errors in writing, especially among students and for people who do not use English as their mother tongue. Because of this, webinars on academic writing are very much needed and should be held frequently in order to improve students' writing knowledge and skills. The ability to write an academic paper is a demand that must be met by every student and lecturer. This ability is not solely related to the procedures and techniques of writing an academic work, but also to the substantial demands attached to it. Complete answers to these two demands will determine the quality of an academic paper. In practice, there are so many cases that show that they have not been understood and the demands attached to an academic paper, both technically and substantively, have not been fulfilled. In fact, there have been many cases where academic integrity has been put aside in favor of short-term goals. A phenomenon that has become increasingly troubling in recent times is the widespread practice of plagiarism that has hit students and lecturers, either on purpose or by ignorance. If this phenomenon is left unchecked, academic integrity as the main pillar supporting the implementation of education will undoubtedly be increasingly shaky, even destroyed one day. Therefore, strategic and sustainable interventions are needed that can go straight to the problem.